Comparison of in vitro Killing Effect of Thai Herbal Essential Oils, Tea Tree Oil, and Metronidazole 0.75% versus Ivermectin 1% on Demodex folliculorum - Paichitrojjana A; Chalermchai T (Dove Medical Press, 2023)
Anon Paichitrojjana, Thep Chalermchai School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Bangkok, ThailandCorrespondence: Thep Chalermchai, School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, 36/87-88 PS Tower 25Fl, Asoke Road, Sukhumvit 21, Klong Toey Nua, Wattana, Bangkok, 10110, Thailand, Tel +66-2-6644360, Email thep_chalermchai@hotmail.comBackground: Abnormal proliferation of Demodex mites causes a skin disorder called demodicosis and has been linked to rosacea. The development of alternative therapy against Demodex mites is currently required. The ability to kill Demodex mites of Thai herbal essential oils has never been explored. This study aimed to study and compare the in vitro killing effect of Thai herbal essential oils, tea tree oil, and metronidazole 0.75% with ivermectin 1% on D. folliculorum.Materials and Methods: D. folliculorum mites were collected from the wastes of diagnostic standardized skin surface biopsy samples of demodicosis and rosacea patients for the trial. The microscopic evaluation started immediately after the mites were exposed to immersion oil (negative control), Thai herbal essential oils, tea tree oil, metronidazole 0.75%, and ivermectin 1% (positive control). The survival times of ten mites from each test agent were compared.Results: The efficacy of Thai herbal essential oils and other test agents can be arranged in order as follows: lemongrass oil > sweet basil oil > clove oil > tea tree oil > lesser galangal oil > ginger oil, kaffir lime oil, peppermint oil > citronella oil > galangal oil > cajeput oil > ivermectin 1% > metronidazole 0.75%.Conclusion: This current study demonstrated the in vitro killing efficacy on D. folliculorum: Thai herbal essential oils, Tea tree oil > ivermectin 1% > metronidazole 0.75%. Thai herbal essential oils have the potential to be an adjuvant or alternative therapy against Demodex mites. Further in vivo studies are necessary to determine the treatment efficacy and side effects.Keywords: essential oils, metronidazole, ivermectin, Demodex mites, demodicosis, rosacea